2007
DOI: 10.1021/ma070702+
|View full text |Cite
|
Sign up to set email alerts
|

Highly Cross-Linked Epoxy Resins:  An Atomistic Molecular Dynamics Simulation Combined with a Mapping/Reverse Mapping Procedure

Abstract: This paper presents a new computational method for simulating polymer network formation. There are four separate procedures involved in the methodology for this multiscale simulation: (i) mapping of the polymerizing monomers onto a coarse-grained model, (ii) cross-linking the monomers by applying Monte Carlo simulation to the coarse-grained model, (iii) reverse mapping of the coarse-grained model to a fully atomistic representation, and (iv) simulation of the atomistic model through standard molecular dynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
136
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(159 citation statements)
references
References 87 publications
12
136
0
Order By: Relevance
“…2(b), has been generated using the pcff force field 81 and implementing the computational procedure suggested in Ref. 82. The fully atomistic representation of the silica surface is taken in the present study in view of the further perspectives of the whole project.…”
Section: Silica Modelmentioning
confidence: 99%
“…2(b), has been generated using the pcff force field 81 and implementing the computational procedure suggested in Ref. 82. The fully atomistic representation of the silica surface is taken in the present study in view of the further perspectives of the whole project.…”
Section: Silica Modelmentioning
confidence: 99%
“…There are two approaches to obtain crosslinked networks: (i) to use representative crosslinked units with a certain degree of crosslinking, then performing classical MD runs for equilibration and data collection 36,53 (ii) to create a simulation box including primary molecules of resin and curing agent without any crosslink, then performing a cyclic set of minimization, equilibration and dynamics runs to reach a crosslinked structure by forming a chemical bond with a probability depending 10 on the reactivity of groups whenever two atoms participating in a crosslink are close in space 2,9,12 .Our previous studies 36,53 indicated that the first approach is ineffective in the construction of 3D complex structures such as epoxy networks due to the equilibration problems and the associated computational cost. Moreover, the effect of nanofillers (nanofibers or nanotubes) on crosslinking is disregarded through this method.…”
Section: Crosslinking Algorithmmentioning
confidence: 99%
“…Computational modelling offers a tool to investigate how strength and stiffness of the composite depend on the degree of cross-linking in the matrix and reinforcement provided by nanofillers. Due to their excellent mechanical and thermal stability neat thermoset epoxy resins have been investigated thoroughly in the literature, and as a matrix, they have been simulated extensively by molecular dynamics (MD) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] . For a proper understanding of their equilibrated structures, there are several attempts which perform coarse-graining to simulate these crosslinked networks on 35 larger time and length scales 2,19,20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These criteria are being integrated into an algorithm that crosslinks the system in a manner similar to the real VE resin curing process. Though several crosslinking algorithms have been proposed for epoxies (Komarov, 2007;Varshney, 2008;Lin and Khare, 2009), no such algorithm exists yet for VE resin that would include the real chemistry of the crosslinking reaction. A robust VE crosslinking algorithm has now been developed as part of this work.…”
Section: Figurementioning
confidence: 99%